Developing an IoT-Based Smart Mini Hydroponic Greenhouse Prototype - Arya Nanda Eka Putra; Marti Widya Sari; Prahenusa Wahyu Ciptadi; R. Hafid Hardyanto; Banu Santoso (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2026)
The development of urban agriculture faces challenges related to limited land availability, water scarcity, and inefficient plant management. These conditions encourage the adoption of smart agricultural technologies that operate automatically and efficiently. This study aims to develop an IoT-based smart mini greenhouse prototype suitable for urban environments with limited space. The research method used is an experimental approach focusing on system design and implementation. The system employs an ESP32 microcontroller as the main control unit and is equipped with pH, Electrical Conductivity, and water temperature sensors to monitor the quality of hydroponic nutrient solutions. Sensor data are automatically processed to control circulation pumps and nutrient correction pumps via relay modules, and the data are transmitted to a web-based monitoring system in real time. The test results show that the system can monitor water quality parameters stably and automatically perform irrigation and nutrient correction according to predefined threshold values. The implementation of this system improves the efficiency of water and nutrient management and reduces reliance on manual monitoring. These results indicate that the IoT-based smart mini greenhouse has the potential to serve as a practical and sustainable solution for supporting urban farming in areas with limited land.